2017
DOI: 10.1177/1087054717690231
|View full text |Cite
|
Sign up to set email alerts
|

Group Treatment for Adults With ADHD Based on a Novel Combination of Cognitive and Dialectical Behavior Interventions: A Feasibility Study

Abstract: ADHD symptoms significantly decreased ( d = 1.29) and remained stable for 6 months. Measures of depression, perceived stress, and anxiety were also significantly reduced. Attendance and patient satisfaction was high. Use, comprehension, and perceived benefit of treatment components varied from medium to high. Total use of treatment components was, in general, positively correlated with favorable outcome. The current combination of treatment components may be a valuable addition to available treatments in psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 117 publications
3
26
1
1
Order By: Relevance
“…Results of repeated measures ANOVAs for the overall treatment effects as well as post hoc t-test examining effects from pretreatment (T1) to posttreatment (T2), and from T1 to 3-month follow-up (T3). When comparing pretreatment symptom levels of participants in the present study with the levels of participants in other group-based intervention studies using the same outcome measures, it is evident that our sample had similar levels of ADHD symptoms (e.g., Nasri et al, 2020), but a higher level of comorbid disorders (Nasri et al, 2020) and poorer quality of life (Morgensterns et al, 2016). Given our recruitment procedure, which involved selecting ADHD patients with especially great difficulties regulating emotions, our patients also had much greater problems in this area (Mitchell et al, 2017;Nasri et al, 2020).…”
Section: Treatment Completionmentioning
confidence: 82%
See 1 more Smart Citation
“…Results of repeated measures ANOVAs for the overall treatment effects as well as post hoc t-test examining effects from pretreatment (T1) to posttreatment (T2), and from T1 to 3-month follow-up (T3). When comparing pretreatment symptom levels of participants in the present study with the levels of participants in other group-based intervention studies using the same outcome measures, it is evident that our sample had similar levels of ADHD symptoms (e.g., Nasri et al, 2020), but a higher level of comorbid disorders (Nasri et al, 2020) and poorer quality of life (Morgensterns et al, 2016). Given our recruitment procedure, which involved selecting ADHD patients with especially great difficulties regulating emotions, our patients also had much greater problems in this area (Mitchell et al, 2017;Nasri et al, 2020).…”
Section: Treatment Completionmentioning
confidence: 82%
“…Previous research examining the efficacy of available psychological treatments for adults with ADHD has not only shown reduction in ADHD symptoms, but also effects on other outcomes such as depression, anxiety, self-esteem and quality of life (reviews by Fullen et al, 2020;Nimmo-Smith et al, 2020). Although emotion regulation has not been the main focus of any of these treatments, some of them have shown improvements with regard to this construct as well (Morgensterns et al, 2016;Mitchell et al, 2017;Nasri et al, 2020). In addition, there are other types of psychological treatment, such as Dialectical Behavior Therapy (DBT; Linehan, 1993aLinehan, , 1993b and Emotion Regulation Group Therapy (ERGT; Gratz et al, 2014), which focus on emotion regulation skills, although these treatments have been developed for, and primarily used with, patients diagnosed with Borderline Personality Disorder or severe self-harming behaviors.…”
Section: Psychological Treatment For Adult Adhdmentioning
confidence: 99%
“…Current evidence on follow-up assessments of cognitive behavioral therapy (CBT) in adults with ADHD is limited in terms of sample size and shorter follow-up periods compared with COMPAS. 6 , 51 , 52 , 53 , 54 , 55 , 56 A 2018 meta-analysis on long-term efficacy of psychosocial treatments for adults with ADHD 57 found evidence of sustained effects of ADHD-specific psychosocial treatment approaches on ADHD symptoms for at least 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, few investigators have examined whether this treatment has benefit for emotional dysregulation. Two small studies have shown promise for treating emotional dysregulation with a combination of CBT and dialectical behavior therapy (DBT) (Cole et al., ; Nasri et al., ). Nasri et al.…”
Section: Effects Of Adhd Treatments On Emotional Dysregulationmentioning
confidence: 99%